Impact of Route Selection Metrics on the Performance of DSR Protocol for MANETs - Abdul Rahman, Mohd Nordin; M. Saleh, Ragb O.; Mohd Saman, Md Yazid (2013)
Mobile Ad-hoc Networks (MANETs) are characterized by connectivity through a group of wireless nodes. MANETs are deployed in circumstances where no base station is available. Accordingly, MANETs need routing protocols which can adopt with dynamic topologies. To achieve this, several routing protocols are proposed and deployed. The route selection is one of the most important method design optimization criterion in routing protocols. Most conventional route selection methods do not consider both the freshness and shortness of the route while selecting routes. In this paper, we present two route selection methods for DSR protocol, which consider the freshness of the route as the primary route selection metric. In addition, we describe the proposed methods and explain their effectiveness via presenting and comparing simulation results with popular DSR protocol. The parameters used for evaluation are packet delivery ratio, routing overhead and dropped packets. The simulations are carried out using GloMoSim simulator.